2012
DOI: 10.1111/evo.12012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Transcription Networks in Response to Temporal Fluctuations

Abstract: Organisms respond to changes in their environment over a wide range of biological and temporal scales. Such phenotypic plasticity can involve developmental, behavioral, physiological, and genetic shifts. The adaptive value of a plastic response is known to depend on the nature of the information that is available to the organism as well as the direct and indirect costs of the plastic response. We modeled the dynamic process of simple gene regulatory networks as they responded to temporal fluctuations in enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Finally, environmental variation is also known to result in correlated variation in mean population traits, as natural selection favors different phenotypes over evolutionary time (adaptive tracking) (12). Although an increasing amount of attention has been recently devoted to the conditions that promote these different forms of evolutionary response to environmental variation (hereafter "response modes") (2, 9, 13-18), most studies have considered only one or a small subset of response modes (16,17), and few have explored the general conditions under which one (or more) may be selected above the others (2,18). Addressing these issues will be critical for improving our ability to predict whether and how populations will adapt to both natural and human-induced environmental change.…”
mentioning
confidence: 99%
“…Finally, environmental variation is also known to result in correlated variation in mean population traits, as natural selection favors different phenotypes over evolutionary time (adaptive tracking) (12). Although an increasing amount of attention has been recently devoted to the conditions that promote these different forms of evolutionary response to environmental variation (hereafter "response modes") (2, 9, 13-18), most studies have considered only one or a small subset of response modes (16,17), and few have explored the general conditions under which one (or more) may be selected above the others (2,18). Addressing these issues will be critical for improving our ability to predict whether and how populations will adapt to both natural and human-induced environmental change.…”
mentioning
confidence: 99%
“…Organisms optimize their growth and thereby their chances of survival by finding a matrix of transition rates that maximizes Λ in fluctuating environments. Predicting this optimum presents a key problem across multiple fields, from biology to control theory and finance [25, 27, 30, 32]. …”
mentioning
confidence: 99%
“…3C, E), and biologically it could correspond to a tuning of interactions among genes in the network (see e.g. [27]).…”
mentioning
confidence: 99%
“…My results suggest that information flow within a module should be selected to minimize signal attenuation; models by Roh et al. () and Draghi and Whitlock () found that gene networks can evolve to reduce stochastic noise in gene expression. Similarly, game theory models show that unimodal signaling will be favored over multimodal signaling absent costs or constraints on signal reliability (Wilson et al.…”
Section: Discussionmentioning
confidence: 92%
“…In my model, loci were completely unlinked, the mutation rate was relatively high, and there was no mechanism for the evolution of noise reduction, such as in the models of Roh et al. () and Draghi and Whitlock ().…”
Section: Discussionmentioning
confidence: 97%